Characterization of shoulder moments and force application in static and dynamic campus exercises - Exel, J.; Satzinger, J.; Koller, W.; Baca, A.; Kainz, H. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
This study aimed to characterize shoulder joint moments and force application patterns in static and dynamic campus exercises. Campus exercises are upper-body plyometric movements performed on a ladder-like training board, where climbers ascend using only their arms, without foot support. Twenty advanced/elite climbers performed five trials of each exercise on an instrumented two-rung campus board. Shoulder joint moments on the 3 planes of motion and vertical forces for each limb were computed across the exercise cycles and time series were compared. Results showed that dynamic campus exercises elicited higher shoulder joint moments in the sagittal and frontal planes, particularly during the mid-cycle transition. In contrast, static campus required sustained force production, leading to higher joint moments in the supporting limb at the moment the reaching hand held the next rung. These findings suggest that static campus emphasizes steady body-control stabilization, whereas dynamic campus relies on power production and coordination.